Feeling time : duration, the novel, and eighteenth-century sensibility - Yahav, Amit S. (University of Pennsylvania Press, 2018)
Feeling Time highlights the temporal underpinnings of the eighteenth century's culture of sensibility, arguing that novelists have often drawn on logics of musical composition to make their writing an especially effective tool for exploring time and for shaping durational experience.